Risk factors leading to cerebral arterial rupture by intravascular balloon. - Schueler, B A; Rüfenacht, D A (American Journal of Neuroradiology, 1993)
PURPOSE To clarify what is safe use of balloons in interventional neuroradiologic procedures.METHODS Critical parameter values of balloon inflation and cerebral artery dilatation and rupture were determined. Dimensions and internal pressure were measured for a variety of latex and silicone balloons during inflation in both unconstrained and constrained environments including glass tubes, cadaveric human cerebral arteries, and canine basilar arteries.RESULTS For unconstrained inflation, pressures within balloons inflated to the recommended maximum volume ranged from 200 to 650 mm Hg. When constrained, pressures became much higher for the same injected fluid volume. Balloon dilatation until artery rupture occurred only for balloons with diameters greater than 2.5 times the unstretched vessel diameter. Balloon pressures at vessel rupture ranged from 1000 to 2000 mm Hg.CONCLUSION Pressures within inflated balloons vary with balloon type, material, degree of inflation, and constraint. Constrained balloons have markedly higher internal pressures, which may lead to vessel rupture if balloons are much larger than the vessel diameter.